PROSPEK PERSEROAN PEMEGANG SAHAM TUNGGAL TANPA PERKECUALIAN UNTUK KEMUDAHAN BISNIS - Efendi, A'an (Veritas et Justitia, 2020)
As a general rule, economic enterprises or companies should be established based on the principle of capital association and agreement.  In contrast, Law No. 40 of 2007 re. Limited Liability Companies, provide exemptions to both principles. On the basis of this observation the issue discussed  in this articles are: (1) why is the exemption provided only for certain forms of economic enterprises or companies; (2) is this exemption to the rule justified, perceived from the principle of equality; and (3) what are the justification for allowing the establishment of a limited liability company with a single investor (sole ownership). Using a juridical doctrinal approach the answer to the above questions are: (1) exemption are granted for state owned companies, established and regulated under public law; (2)  the exemption is unjust as it discriminates and allowed for discriminative treatment; and (3) the practice of establishing a limited liability company by a single shareholder is a long standing practice.